Age cohorts stratified according to age-distributions of COVID-19 morbidity statistics identify uniquely age-dependent CD3(+)CD8(+) T-cell lymphocytopenia in COVID-19 patients without comorbidities on admission - Jin, Shengwei (Aging (Albany NY), 2021)
If age boundaries are arbitrarily or roughly defined, age-related analyses can result in questionable findings. Here, we aimed to delineate the uniquely age-dependent immune features of coronavirus disease 2019 (COVID-19) in a retrospective study of 447 patients, stratified according to age distributions of COVID-19 morbidity statistics into well-defined age-cohorts (2–25y, 26–38y, 39–57y, 58–68y, and 69–79y). Age-dependent susceptibilities and severities of the disease were observed in COVID-19 patients. A comparison of the lymphocyte counts among the five age-groups indicated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection led to age-dependent lymphopenia. Among the lymphocyte subsets, the CD8(+) T cell count alone was significantly and age-dependently decreased (520, 385, 320, 172, and 139 n/μl in the five age-groups, respectively). In contrast, the CD4(+) T cell, B cell, and natural killer cell counts did not differ among age-cohorts. Age and CD8(+) T cell counts (r=‒0.435, p<0.0001) were negatively correlated in COVID-19 patients. Moreover, SARS-CoV-2 infection age-dependently increased the plasma C-reactive protein concentrations (2.0, 5.0, 9.0, 11.6, and 36.1 mg/L in the five age-groups, respectively). These findings can be used to elucidate the role of CD8(+) T cells in age-related pathogenesis and to help develop therapeutic strategies for COVID-19.